Flow distribution of hydrocarbon fuel in parallel minichannels heat exchanger. Issue 7 (25th January 2018) - Chen, Yu; Lei, Zhiliang; Zhang, Tianhao; Zhu, Quan; Bao, Zewei; Zhang, Qiyi; Li, Xiang‐Yuan
Abstract : In this article, the flow distribution of the Chinese No. 3 jet fuel in parallel minichannels heat exchanger under high temperature condition was investigated. The models of PFR and choked flow were established based on the real fluid model. The formation mechanism of flow maldistribution of the fuel in the freely distributed channels was studied. It was found that: under low heat flux, the slight flow rate deviation will be spontaneously eliminated; under high heat flux, the slight deviation of flow rate and heat flux will be enlarged and result in the channel with smaller flow rate entering the coking region. The feasibility and influence factors of the control method of flow distribution based on choked flow were discussed. The experimental results indicated that the minichannels fuel‐cooled plate with choked flow could maintain uniform flow distribution when the total fuel outlet temperature reached 1035 K. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2781–2791, 2018